Answer:
729/4096
Explanation:
Simplify the following:
(3/4)^5 3/4
(3/4)^5 3/4 = ((3/4)^5 3)/4:
((3/4)^5 3)/4
(3/4)^5 = 3^5/4^5:
(3^5/4^5 3)/4
3^5 = 3×3^4 = 3 (3^2)^2:
((3 (3^2)^2)/4^5 3)/4
4^5 = 4×4^4 = 4 (4^2)^2:
((3 (3^2)^2)/(4 (4^2)^2) 3)/4
4^2 = 16:
((3 (3^2)^2)/(4×16^2) 3)/4
3^2 = 9:
((3×9^2)/(4×16^2) 3)/4
| 1 | 6
× | 1 | 6
| 9 | 6
1 | 6 | 0
2 | 5 | 6:
((3×9^2)/(4×256) 3)/4
9^2 = 81:
((3×81)/(4×256) 3)/4
4×256 = 1024:
((3×81)/1024×3)/4
3×81 = 243:
(243/1024×3)/4
243/1024×3 = (243×3)/1024:
((243×3)/1024)/4
((243×3)/1024)/4 = (243×3)/(1024×4):
(243×3)/(1024×4)
1024×4 = 4096:
(243×3)/4096
243×3 = 729:
Answer: 729/4096